UNVEILING MASCULINE SILENCE: REFLECTIONS ON IDENTITY AND CARE - Sá, Anderson Alexandre Araújo (Seven Editora, 2025)
This article investigates male discourses surrounding the construction of gender identity and care, using as a basis the narratives presented in the documentary "The Silence of Men". The research explores how normative discourses, perpetuated since childhood, contribute to the formation of emotional barriers in men, making it difficult to express feelings and open up to vulnerability. The impacts of hegemonic masculinity and how this structure affects both men and their interpersonal relationships are analyzed, addressing topics such as gender violence, emotional repression, and resistance to care. The study also highlights initiatives to deconstruct hegemonic patterns, emphasizing the importance of reflective practices and the active involvement of men in the ethics of care. The qualitative methodology, based on content analysis, allowed the identification of three thematic categories: discourses on being a man, violence and hegemonic masculinity, and protagonists and practices of care. The results point to the need to rethink masculinities from a critical perspective, promoting care as an essential component for gender equity and emotional well-being.DOI: https://doi.org/10.56238/sevened2024.037-164